Different Pathological Roles of Toll-Like Receptor 9 on Mucosal B Cells and Dendritic Cells in Murine IgA Nephropathy. (30th June 2011) - Kajiyama, Tadahiro; Suzuki, Yusuke; Kihara, Masao; Suzuki, Hitoshi; Horikoshi, Satoshi; Tomino, Yasuhiko
Abstract : Although pathogenesis of IgA nephropathy (IgAN) is still obscure, pathological contribution of mucosal immunity including production of nephritogenic IgA and IgA immune complex (IC) has been discussed. We have reported that mucosal toll-like receptor (TLR)-9 is involved in the pathogenesis of human and murine IgAN. However, cell-type expressing TLR9 in mucosa remains unclear. To address this, we nasally challenged cell-specific CpG DNA ((i): dendritic cell: (DC), (ii): B cell, (iii): both), known as ligand for TLR9, to IgAN prone mice and analyzed disease phenotype of each group. After 8 times of the weekly administration, every group showed deterioration of glomerular damage. However, CpG-A-group showed clear extension of mesangial proliferative lesions with increase of serum IgA-IgG2a IC and its glomerular depositions, while CpG-B-group showed extent of glomerular sclerotic lesions with increase of serum and glomerular IgA and M2 macrophage infiltration. Present results indicate that mucosal TLR9 on B cells and DC may differently contribute to the progression of this disease via induction of nephritogenic IgA or IgA-IgG IC, respectively. This picture is suggestive for the pathological difference between child and adult IgAN.